Independent Reading of Adapted Science Texts in Teaching Russian as Foreign Language: Student Motivation - Abramova, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Many studies in the field of second and foreign language learning have focused on student motivation and the factors affecting it. Likewise, positive motivation is essential for individual learning and a key factor in successful individual reading in a foreign (second) language. Most teachers believe that science texts are more challenging for L2 learners; consequently, the issue of facilitating L2 learners’ motivation is highly significant in reading instruction. The objective of the currant research is to find out if the factors creating and maintaining foreign learners’ reading motivation are used in Russian language textbooks, in particular, in the structure of reading exercises. The paper includes a review of literature on motivation factors in individual reading and foreign language learning and provides an analysis of reading exercises of 25 Russian language textbooks in the context of reading motivation.